AN INVESTIGATION OF THE EFFECT OF INTERNAL MARKETING ON THE STRATEGIC COMPETITIVE ADVANTAGE OF BANKING FIRMS IN KENYA - Kanario, Purity; Kamaria, Prof. Joe K. (European Journal of Business and Strategic Management, 2016)
Purpose: The purpose of this study was to investigate the effect of internal marketing on the strategic competitive advantage of banking firms in Kenya. Methodology: The research design was a descriptive survey study in nature since it allows a methodical choice of samples and a rigorous analysis of data. The target population of this study was all the commercial banks in Kenya. Both qualitative and quantitative data was used to collect data using a questionnaire that consisted of both open ended close ended questions. Inferential statistics such as correlation were used. Data was analyzed using Statistical Package for Social Sciences (SPSS) and results were presented in frequency tables to show how the responses for the various questions posed to the respondents. Results: Results indicated that majority of the respondents agreed that customer orientation had effect on the strategic competitive advantage. Correlation results indicated that the relationship between customer orientation and competitive advantage was positive. Results indicated that majority of the respondents agreed that employee empowerment had effect on the strategic competitive advantage. Correlation results indicated that the relationship between employee empowerment and strategic competitive advantage was positive and significant. Results indicated that majority of the respondents agreed that employee satisfaction had effect on strategic competitive advantage. Correlation results indicated that the relationship between employee satisfaction and strategic competitive advantage was positive and significant. The study concludes that customer orientation practices were highly emphasized in the banks. It Unique contribution to theory, practice and policy: Following study results, it is recommended that customer orientation practices be continued emphasized in the banks as it has an effect on the overall achievement of strategic competitive advantage. It is also recommended that employee empowerment be emphasized in the banks as it has an effect on the overall achievement of strategic competitive advantage. It is also recommended that the management to encourage autonomous action among staff and the management also to encourage the developing of a clear vision. It is recommended that employee satisfaction.